Process and device for purifying high-purity isopropanol

By using a three-layer composite film of crown ether modified polyimide-nanofiber film-sodium alginate composite film for permeation and gasification in the isopropanol purification process, it is solved that it is difficult to remove metal ions in isopropanol in the prior art. and moisture problems achieve high purity and low energy consumption isopropanol purification effect.

CN119462340AInactive Publication Date: 2025-02-18JIANGSU MEIYANG ELECTRONIC MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411446341.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when preparing electronic grade isopropanol, it is difficult to effectively remove metal ions, dust particles and moisture, resulting in low product quality and cannot meet the production needs of high-grade electronic grade isopropanol.

Method used

Using a purification process of high-purity isopropanol, including ion exchange, heating, permeability, circulation distillation and filtration, three-layer composite of polyimide-nanofiber film-sodium alginate with crown ether modified The film is permeable and gasified to remove metal ions and moisture from isopropanol.

Benefits of technology

It significantly reduces the metal ions and moisture content in isopropyl alcohol, improves the purity and quality of the product, meets the production needs of high-grade electronic grade isopropyl alcohol, and reduces energy consumption and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462340A_ABST
    Figure CN119462340A_ABST
Patent Text Reader

Abstract

The invention provides a process and a device for purifying high-purity isopropanol. Impurities such as metal ions, water and particles are efficiently removed by adopting the technological processes such as ion exchange, pervaporation, distillation and filtration, the prepared electronic-grade isopropanol can reach 99.9% or above, the content of each metal ion is smaller than 1 ppb, and the application requirements of the microelectronic industry are met. The electronic-grade isopropanol produced by adopting the process flow and the equipment disclosed by the invention is high in yield, stable in product quality and high in practicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic-grade chemical preparation, and particularly relates to a purification process and a device for high-purity isopropanol. Background Art

[0002] Electronic grade isopropyl alcohol is one of the wet electronic chemicals used in the microelectronics industry. It can be used to clean silicon wafers, effectively remove impurity particles, inorganic residues and carbon deposits on the wafers, and is widely used in the production of photovoltaic solar cells, flat panel displays, integrated circuits and other electronic components.

[0003] During the production, transportation and storage of isopropyl alcohol, due to raw materials and equipment reasons, some metal ions, dust particles, unreacted raw materials and intermediate products are inevitably introduced into the product, and these impurities can easily lead to the generation of staggered layers, resulting in PN combination leakage current, breakdown, etc. For integrated circuits with smaller line widths, even a small amount of metal ions and particles may destroy the entire circuit. Therefore, with the rapid development of integrated circuits, the requirements for the purity of electronic-grade reagents are getting higher and higher. How to effectively remove metal ions and dust particles is a technical problem that needs to be solved urgently.

[0004] CN103848718A discloses a method for preparing electronic-grade isopropyl alcohol by using an ion exchange fiber and microporous membrane coupling column. The method comprises using anion and cation exchange fibers treated with hydrochloric acid, sodium hydroxide and ultra-high purity water as adsorbents for trace metal ions and non-metal ions in isopropyl alcohol, and a microporous membrane to form an anion and cation exchange fiber and microporous membrane coupling column. Isopropyl alcohol is passed through the cation exchange fiber and microporous membrane coupling column and the anion exchange fiber and microporous membrane coupling column. After sufficient contact and adsorption, trace metal ions and non-metal ions in the isopropyl alcohol are removed to obtain electronic chemical isopropyl alcohol. However, the method has high requirements on the purity of raw materials.

[0005] In general, the existing disclosed preparation processes have low removal efficiency for impure metals, particles and water, high energy consumption, and cannot meet the production of high-grade electronic-grade isopropyl alcohol and the needs of large-scale production. Summary of the invention

[0006] The invention provides a purification process and a device for high-purity isopropyl alcohol, aiming to provide a new and efficient method, reduce the content of impurities such as metals, particles, water and the like in electronic-grade isopropyl alcohol, improve the quality of the electronic-grade isopropyl alcohol and meet customer needs.

[0007] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a purification process for high-purity isopropanol. To achieve the above technical objectives, the technical solution adopted by the present invention is:

[0008] A purification process for high-purity isopropanol comprises the following steps:

[0009] (1) Ion exchange: Industrial-grade isopropyl alcohol is subjected to ion exchange through cation exchange resin and anion exchange resin respectively;

[0010] (2) Heating: heating the isopropanol that has passed through the anion exchange resin;

[0011] (3) Pervaporation: The heated isopropyl alcohol is supplied to the pervaporation membrane assembly to further remove metal ions and moisture;

[0012] (4) Circulation and distillation: A portion of the non-permeated liquid in step (3) is supplied to a distillation device for distillation, and another portion of the non-permeated liquid is heated through a circulation pipe and supplied to the pervaporation membrane module again. The amount of liquid supplied to the pervaporation membrane module through circulation is more than 8 times the volume of the liquid supplied to the pervaporation membrane module directly after ion exchange.

[0013] (5) The distilled isopropyl alcohol is filtered to obtain high-purity isopropyl alcohol.

[0014] Wherein, the pervaporation membrane is a three-layer composite film of crown ether-modified polyimide-nanofiber film-sodium alginate.

[0015] The present invention adopts pervaporation membrane technology to remove metal ions and water in isopropanol. It is unexpectedly found that metal ions and other anions such as sulfate ions have an important influence on the pervaporation membrane material sodium alginate and its performance and service life in high-temperature isopropanol. Even after the metal ions and anions in isopropanol are mostly removed through ion exchange resin, their trace components still have an influence on the pervaporation membrane.

[0016] A three-layer composite film of crown ether-modified polyimide-nanofiber film-sodium alginate is used. The crown ether-modified polyimide and nanofiber film can further remove metal ions and reduce the contact between isopropyl alcohol and sodium alginate. The nanofiber membrane has high mechanical strength and is firmly composited with sodium alginate, which can effectively support the sodium alginate film and prevent the sodium alginate film from being damaged.

[0017] Preparation method of composite film:

[0018] The first step is to prepare a polyamic acid solution grafted with a crown ether, react a diamine monomer with a dianhydride monomer at a low temperature to form a polyamic acid solution. The diamine monomer raw material is a mixture of a diamine containing a crown ether compound group and other aromatic diamine monomers.

[0019] Step 2: Add dehydrating agent and catalyst to the polyamic acid solution, heat and polymerize. Dissolve the polymerized product in an organic solvent, coat it on the nanofiber film, and remove the solvent to form a crown ether modified polyimide-nanofiber film.

[0020] Step 3: coating the sodium alginate aqueous solution on the nanofiber membrane to prepare a hydrogel layer, cross-linking, and drying to obtain a crown ether modified polyimide-nanofiber membrane-sodium alginate three-layer composite film.

[0021] The thickness of the sodium alginate film is controlled between 600nm and 800nm.

[0022] The diamine compound containing a crown ether group is diaminodibenzo-18-crown-6.

[0023] Another diamine compound is 4,4'-diaminodiphenylmethane.

[0024] The dianhydride is 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.

[0025] Optionally, in step (1), when passing through a cation exchange resin, the temperature of the isopropanol liquid is 40-60°C, and when passing through an anion exchange resin, the temperature is 50-70°C.

[0026] Optionally, the concentration of industrial-grade isopropanol in step (1) is greater than or equal to 80%, more preferably greater than or equal to 90%.

[0027] Optionally, the heating temperature in step (2) is 60-80°C, more preferably 60-75°C.

[0028] Optionally, the concentration of the high purity isopropyl alcohol is greater than or equal to 99.9%.

[0029] Optionally, the nanofiber membrane is made of a material containing a hydrophilic polymer.

[0030] Optionally, the nanofiber film is a cellulose nanofiber film.

[0031] The material of the nanofiber film affects the combination of sodium alginate and the nanofiber film, and thus affects its service life. For example, in a short period of time, the sodium alginate and the fiber film will be peeled off and fail.

[0032] Preferably, the nanofiber film is modified by low-temperature plasma. The inventors found that the nanofiber film modified by plasma can increase the roughness of the fiber surface and conduct it to the crown ether-modified polyimide surface, which can improve the adsorption and removal effect of metal ions. The concentration of metal ions such as Fe, Cu, and Ti can generally be reduced by 0.1 ppb.

[0033] In addition, the present invention also provides a device for producing high-purity isopropyl alcohol, comprising a cation exchange column, an anion exchange column, a heating device, a pervaporation device, a distillation device, a filtering device, and a container connected in sequence; the pervaporation device comprises a pervaporation membrane, isopropyl alcohol is transported to one side of the pervaporation membrane, and the other side is connected to a vacuum pump through a discharge pipe to control the pressure, non-permeated liquid is collected and transported, a part of the non-permeated liquid is extracted from the pipeline and supplied to the distillation device, and the rest is sent to the heating device through a circulation pipeline for reheating, and then circulated to the pervaporation device; the pervaporation membrane is a crown ether modified polyimide-nanofiber film-sodium alginate three-layer composite film.

[0034] Preferably, the filter membrane is an electronic grade filter membrane.

[0035] Preferably, a heating device is provided before the cation exchange column or the anion exchange column.

[0036] Compared with the prior art, the present invention has the following advantages and beneficial effects.

[0037] (1) The process and equipment used in the present invention have high output and stable product quality for producing high-purity isopropyl alcohol, are convenient for industrial production, and are highly practical.

[0038] (2) The pervaporation method reduces the number of distillations and energy consumption, and the separation process is simple and does not cause additional environmental pollution.

[0039] (3) The present invention uses a specific pervaporation membrane for pervaporation, which has excellent mechanical strength, high water selective permeability, and can assist in removing metal ions, thereby improving the quality grade of high-purity isopropyl alcohol.

[0040] (4) The permeation vaporization membrane adopts a three-layer composite structure of a specific crown ether-modified polyimide-nanofiber film-sodium alginate. The polyimide membrane and the nanofiber membrane first contact the isopropanol to be purified to remove metal ions, thereby extending the service life of the permeation vaporization membrane.

[0041] (5) The nanofiber film is modified by low-temperature plasma. The plasma-modified nanofiber film can increase the roughness of the fiber surface and transmit it to the crown ether-modified polyimide surface, thereby improving the adsorption and removal effect of metal ions.

[0042] (6) By adopting a circulating supply method, the amount of liquid supplied to the pervaporation membrane module is more than 8 times the volume of the liquid supplied to the pervaporation membrane module after ion exchange, which can more accurately control the temperature supplied to the membrane module and inhibit the temperature drop caused by evaporation. The temperature drop is controlled below 5°C, which can effectively improve the permeation rate and the quality of isopropyl alcohol. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 It is a purification device for high-purity isopropyl alcohol, wherein: 1 - a cation exchange column; 2 - anion exchange column; 3 - a heating device; 4 - a pervaporation device; 5 - a distillation device; 6 - a filtering device; 7 - a container; 8 - a pervaporation membrane; 9 - a pipeline; 10 - a circulation pipeline; 11 - a vacuum pump. DETAILED DESCRIPTION

[0044] The following embodiments are merely examples covered by the present invention and do not constitute any limitation to the scope of implementation.

[0045] Example 1

[0046] A purification process for high-purity isopropanol, which uses Figure 1 This is achieved by the device shown.

[0047] Specifically, the concentration of 95% of industrial-grade isopropyl alcohol is respectively passed through a cation exchange column 1 and an anion exchange column 2 to remove metal ions and anions and cations such as sulfate, halogen ions, and nitrate ions in the isopropyl alcohol. The isopropyl alcohol liquid after ion exchange is sent to a heating device 3, and the isopropyl alcohol liquid is heated to 68°C. After heating, the isopropyl alcohol liquid is transported to one side of a permeation vaporization membrane 8, and the other side is connected to a vacuum pump 11 through a discharge pipe to control the pressure to 15KPa. Water in the isopropyl alcohol liquid permeates the permeation vaporization membrane 8, and the non-permeated liquid is collected and transported to a pipeline 9. A part of the non-permeated liquid is extracted from the pipeline 9 and supplied to a distillation device 5, and the rest is sent to the heating device 3 through a circulation pipeline 10 for reheating, and then circulated to the permeation vaporization device 4, and the amount of liquid circulating through the membrane is more than 8 times the volume of the newly supplied liquid. The fraction of 82.2-82.5°C is collected by distillation, and filtered through an electronic grade filter to obtain high-purity isopropyl alcohol.

[0048] The structure of the pervaporation membrane is a three-layer composite film of crown ether-modified polyimide-nanofiber film-sodium alginate.

[0049] Preparation method of composite film: under protective atmosphere, diamine monomer is added to organic solvent N, N-dimethylacetamide, and the molar ratio of diamine to dianhydride is 1:1. At 18°C, dianhydride is added to diamine solution to prepare a mixed solution and stir for 12 hours to react to form a polyamic acid solution. Then, dehydrating agent acetic anhydride and catalyst triethylamine are added to the polyamic acid solution, and the solvent is removed after stirring at 110°C for 6 hours to obtain a polymer; diamine is a mixture of crown ether compound and other aromatic diamine monomers in a molar ratio of 0.2:1.

[0050] The polyimide polymer was dissolved in an organic solvent and spin-coated on the nanocellulose film. After further removal of the solvent, a crown ether-modified polyimide-nanocellulose film was formed. A 1.5% sodium alginate aqueous solution was scraped on the nanofiber membrane to prepare a hydrogel layer, and then the composite membrane was infiltrated with CaCl 2 The cross-linking is carried out in the process, and after drying, a crown ether modified polyimide-nanocellulose film-sodium alginate three-layer composite film is obtained, and the thickness of the sodium alginate film is controlled between 600nm and 800nm.

[0051] The diamine compound is a mixture of diaminodibenzo-18-crown-6 and 4,4'-diaminodiphenylmethane.

[0052] The dianhydride is 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.

[0053] The amount of liquid supplied by circulation is more than 8 times the volume of the newly supplied liquid. This means that when the working state is stable, that is, after the purification device has been working for a period of time, the amount of liquid supplied by circulation is more than 8 times the volume of the newly supplied liquid. Circulation supply means that after passing through the pervaporation membrane, the isopropanol enters the circulation pipeline and enters the heating device again. The new supply directly enters the heating device after passing through the ion exchange resin column.

[0054] Example 2

[0055] A purification process for high-purity isopropanol, which uses Figure 1 This is achieved by the device shown.

[0056] Specifically, the concentration of 95% industrial grade isopropyl alcohol is heated to 50°C, and passes through a cation exchange column 1 and an anion exchange column 2 respectively to remove metal ions and anions and cations such as sulfate, halogen ions, and nitrate ions in the isopropyl alcohol. The isopropyl alcohol liquid after ion exchange is sent to a heating device 3, and the isopropyl alcohol liquid is heated to 68°C. After heating, the isopropyl alcohol liquid is transported to one side of a permeation vaporization membrane 8, and the other side is connected to a vacuum pump 11 through a discharge pipe to control the pressure to 16KPa. Water in the isopropyl alcohol liquid permeates the permeation vaporization membrane 8, and the non-permeated liquid is collected and transported to a pipeline 9. A part of the non-permeated liquid is extracted from the pipeline 9 and supplied to a distillation device 5, and the rest is sent to the heating device 3 through a circulation pipeline 10 for reheating, and then circulated to the permeation vaporization device 4, and the amount of liquid circulating through the membrane is more than 8 times the volume of the newly supplied liquid. The fraction of 82.2-82.5°C is collected by distillation, and filtered through an electronic grade filter to obtain high-purity isopropyl alcohol.

[0057] The structure of the pervaporation membrane is a three-layer composite film of crown ether-modified polyimide-nanofiber film-sodium alginate.

[0058] Preparation method of composite film: under protective atmosphere, diamine monomer is added to organic solvent N, N-dimethylacetamide, and the molar ratio of diamine to dianhydride is 1:1. At 18°C, dianhydride is added to diamine solution to prepare a mixed solution and stir for 12 hours to react to form a polyamic acid solution. Then, dehydrating agent acetic anhydride and catalyst triethylamine are added to the polyamic acid solution, and the solvent is removed after stirring at 110°C for 6 hours to obtain a polymer; diamine is a mixture of crown ether compound and other aromatic diamine monomers in a molar ratio of 0.2:1.

[0059] The polyimide polymer was dissolved in an organic solvent and spin-coated on the nanocellulose film. After further removal of the solvent, a crown ether-modified polyimide-nanocellulose film was formed. A 1.5% sodium alginate aqueous solution was scraped on the nanofiber membrane to prepare a hydrogel layer, and then the composite membrane was infiltrated with CaCl 2 The cross-linking is carried out in the process, and after drying, a crown ether modified polyimide-nanocellulose film-sodium alginate three-layer composite film is obtained, and the thickness of the sodium alginate film is controlled between 600nm and 800nm.

[0060] The diamine compound is a mixture of diaminodibenzo-18-crown-6 and 4,4'-diaminodiphenylmethane.

[0061] The dianhydride is 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.

[0062] The amount of liquid supplied by circulation is more than 8 times the volume of the newly supplied liquid. This means that when the working state is stable, that is, after the purification device has been working for a period of time, the amount of liquid supplied by circulation is more than 8 times the volume of the newly supplied liquid. Circulation supply means that after passing through the pervaporation membrane, the isopropanol enters the circulation pipeline and enters the heating device again. The new supply directly enters the heating device after passing through the ion exchange resin column.

[0063] Comparative Example 1

[0064] A purification process for high-purity isopropanol, which uses Figure 1 This is achieved by the device shown.

[0065] Specifically, the concentration of 95% of industrial-grade isopropyl alcohol is respectively passed through a cation exchange column 1 and an anion exchange column 2 to remove metal ions and anions and cations such as sulfate, halogen ions, and nitrate ions in the isopropyl alcohol. The isopropyl alcohol liquid after ion exchange is sent to a heating device 3, and the isopropyl alcohol liquid is heated to 68°C. After heating, the isopropyl alcohol liquid is transported to one side of a permeation vaporization membrane 8, and the other side is connected to a vacuum pump 11 through a discharge pipe to control the pressure to 15KPa. Water in the isopropyl alcohol liquid permeates the permeation vaporization membrane 8, and the non-permeated liquid is collected and transported to a pipeline 9. A part of the non-permeated liquid is extracted from the pipeline 9 and supplied to a distillation device 5, and the rest is sent to the heating device 3 through a circulation pipeline 10 for reheating, and then circulated to the permeation vaporization device 4, and the amount of liquid circulating through the membrane is more than 8 times the volume of the newly supplied liquid. The fraction of 82.2-82.5°C is collected by distillation, and filtered through an electronic grade filter to obtain high-purity isopropyl alcohol.

[0066] The structure of the pervaporation membrane is a three-layer composite film of polyimide-nanofiber film-sodium alginate.

[0067] Preparation method of composite film: under protective atmosphere, diamine monomer is added to organic solvent N, N-dimethylacetamide, and the molar ratio of diamine to dianhydride is 1:1. At 18°C, dianhydride is added to diamine solution to prepare a mixed solution and stir for 12 hours to react to form a polyamic acid solution. Then, dehydrating agent acetic anhydride and catalyst triethylamine are added to the polyamic acid solution, and the solvent is removed after stirring at 110°C for 6 hours to obtain a polymer.

[0068] The polyimide polymer was dissolved in an organic solvent and spin-coated on the nanocellulose film. After further removal of the solvent, a polyimide-nanocellulose film was formed. A 1.5% sodium alginate aqueous solution was scraped on the nanofiber membrane to prepare a hydrogel layer, and then the composite membrane was infiltrated with CaCl 2 The polyimide-nanocellulose film-sodium alginate three-layer composite film is obtained after cross-linking and drying, and the thickness of the sodium alginate film is controlled between 600nm and 800nm.

[0069] The diamine compound is 4,4'-diaminodiphenylmethane.

[0070] The dianhydride is 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.

[0071] Comparative Example 2

[0072] A purification process for high-purity isopropanol, which uses Figure 1 This is achieved by the device shown.

[0073] Specifically, the concentration of 95% of industrial-grade isopropyl alcohol is respectively passed through a cation exchange column 1 and an anion exchange column 2 to remove metal ions and anions and cations such as sulfate, halogen ions, and nitrate ions in the isopropyl alcohol. The isopropyl alcohol liquid after ion exchange is sent to a heating device 3, and the isopropyl alcohol liquid is heated to 68°C. After heating, the isopropyl alcohol liquid is transported to one side of a permeation vaporization membrane 8, and the other side is connected to a vacuum pump 11 through a discharge pipe to control the pressure to 15KPa. Water in the isopropyl alcohol liquid permeates the permeation vaporization membrane 8, and the non-permeated liquid is collected and transported to a pipeline 9. A part of the non-permeated liquid is extracted from the pipeline 9 and supplied to a distillation device 5, and the rest is sent to the heating device 3 through a circulation pipeline 10 for reheating, and then circulated to the permeation vaporization device 4, and the amount of liquid circulating through the membrane is more than 8 times the volume of the newly supplied liquid. The fraction of 82.2-82.5°C is collected by distillation, and filtered through an electronic grade filter to obtain high-purity isopropyl alcohol.

[0074] The structure of the pervaporation membrane is a three-layer composite film of crown ether-modified polyimide-nanofiber film-sodium alginate.

[0075] Preparation method of composite film: under protective atmosphere, diamine monomer is added to organic solvent N, N-dimethylacetamide, and the molar ratio of diamine to dianhydride is 1:1. At 18°C, dianhydride is added to diamine solution to prepare a mixed solution and stir for 12 hours to react to form a polyamic acid solution. Then, dehydrating agent acetic anhydride and catalyst triethylamine are added to the polyamic acid solution, and the solvent is removed after stirring at 110°C for 6 hours to obtain a polymer; diamine is a mixture of crown ether compound and other aromatic diamine monomers in a molar ratio of 0.2:1.

[0076] The polyimide polymer was dissolved in an organic solvent and spin-coated on a ceramic fiber film. After further removal of the solvent, a crown ether-modified polyimide-ceramic fiber film was formed. A 1.5% sodium alginate aqueous solution was scraped on the ceramic fiber film to prepare a hydrogel layer. The composite film was then infiltrated with CaCl 2 The cross-linking is carried out in the process, and after drying, a crown ether modified polyimide-ceramic fiber film-sodium alginate three-layer composite film is obtained, and the thickness of the sodium alginate film is controlled between 600nm and 800nm.

[0077] The diamine compound is a mixture of diaminodibenzo-18-crown-6 and 4,4'-diaminodiphenylmethane.

[0078] The dianhydride is 4,4'-(hexafluoroisopropylidene)diphthalic anhydride.

[0079] Comparative Example 3

[0080] A purification process for high-purity isopropanol, which uses Figure 1 This is achieved by the device shown.

[0081] Specifically, the concentration of 95% of industrial-grade isopropyl alcohol is respectively passed through a cation exchange column 1 and an anion exchange column 2 to remove metal ions and anions and cations such as sulfate, halogen ions, and nitrate ions in the isopropyl alcohol. The isopropyl alcohol liquid after ion exchange is sent to a heating device 3, and the isopropyl alcohol liquid is heated to 68°C. After heating, the isopropyl alcohol liquid is transported to one side of a permeation vaporization membrane 8, and the other side is connected to a vacuum pump 11 through a discharge pipe to control the pressure to 15KPa. Water in the isopropyl alcohol liquid permeates the permeation vaporization membrane 8, and the non-permeated liquid is collected and transported to a pipeline 9. A part of the non-permeated liquid is extracted from the pipeline 9 and supplied to a distillation device 5, and the rest is sent to the heating device 3 through a circulation pipeline 10 for reheating, and then circulated to the permeation vaporization device 4, and the amount of liquid circulating through the membrane is more than 8 times the volume of the newly supplied liquid. The fraction of 82.2-82.5°C is collected by distillation, and filtered through an electronic grade filter to obtain high-purity isopropyl alcohol.

[0082] The structure of the pervaporation membrane is a sodium alginate-nanofiber film composite film.

[0083] Preparation method of composite film: 1.5% sodium alginate aqueous solution is used to prepare a hydrogel layer on the nanocellulose film using a scraper, and then the composite film is infiltrated into CaCl 2 The cross-linking is carried out in the reaction mixture, and after drying, a sodium alginate (contacting isopropanol solution)-nanocellulose film composite film is obtained, and the thickness of the sodium alginate film is controlled between 600nm and 800nm.

[0084] Determination method:

[0085] Isopropanol mass fraction: measured using a Karl Fischer moisture meter.

[0086] Determination of metal ion mass fraction: Determination by inductively coupled plasma mass spectrometry (ICP-MS). Weigh 5g of sample to an accuracy of 0.01g, slowly put it into a 50mL volumetric flask containing a small amount of ultrapure water, cool to room temperature, dilute to scale with water, and shake well. Determine the signal intensity of each element in the sample under the same analytical conditions as the standard solution series, and perform a blank test at the same time.

[0087] Particle size determination: The particle size was determined using a laser liquid particle counter.

[0088] Determination of life span: Isopropyl alcohol is purified using a high-purity isopropyl alcohol purification device. Specifically, the purification device is operated continuously for 24 hours, and then repaired for 12 hours. The pervaporation membrane is inspected to determine whether the membrane is peeled off or perforated. On the other hand, the pervaporation membrane is determined to be ineffective based on the test results of isopropyl alcohol concentration and metal ions.

[0089] The mass fraction of isopropanol, metal ions, and particles are all measured when the composite film is not invalid.

[0090] See Table 1 for specific test data:

[0091]

[0092]

[0093] The above embodiments and test data are only some applications and implementations of the present invention, and cannot limit the protection scope of the present invention. Through the above description, any technician in the relevant technical field can see that the present invention is innovated by adopting novel ideas and means, and has obvious practicality and creativity.

Claims

1. A purification process for high-purity isopropanol, comprising the following steps: (1) Ion exchange: Industrial-grade isopropyl alcohol is subjected to ion exchange through cation exchange resin and anion exchange resin respectively; (2) Heating: heating the isopropanol that has passed through the anion exchange resin; (3) Pervaporation: The heated isopropyl alcohol is supplied to the pervaporation membrane assembly to further remove metal ions and moisture; (4) Circulation and distillation: A portion of the non-permeated liquid in step (3) is supplied to a distillation device for distillation, and another portion of the non-permeated liquid is heated through a circulation pipe and supplied to the pervaporation membrane module again. The amount of liquid supplied to the pervaporation membrane module through circulation is more than 8 times the volume of the liquid supplied to the pervaporation membrane module directly after ion exchange. (5) filtering the distilled isopropyl alcohol to obtain high-purity isopropyl alcohol; Wherein, the pervaporation film is a three-layer composite film of crown ether-modified polyimide-nanofiber film-sodium alginate.

2. The process according to claim 1, characterized in that: In the step (1), the temperature of the isopropanol liquid is 40-60°C when passing through the cation exchange resin, and the temperature is 50-70°C when passing through the anion exchange resin.

3. The process according to claim 1, characterized in that: The concentration of industrial grade isopropanol in step (1) is greater than or equal to 80%.

4. The process according to claim 2, characterized in that: The heating temperature in step (2) is 60-75°C.

5. The process according to claim 1, characterized in that: The concentration of the high-purity isopropyl alcohol is greater than or equal to 99.9%.

6. The process according to claim 1, characterized in that: The nanofiber film is a nanocellulose film.

7. The process according to claim 1, characterized in that: Optionally, the nanofiber film is modified by low-temperature plasma.

8. A device for producing high-purity isopropyl alcohol by the process of claim 1, comprising a cation exchange column (1), an anion exchange column (2), a heating device (3), a pervaporation device (4), a distillation device (5), a filtering device (6), and a container (7) connected in sequence; the pervaporation device comprises a pervaporation membrane (8), isopropyl alcohol is transported to one side of the pervaporation membrane, and the other side is connected to a vacuum pump (11) through a discharge pipe to control the pressure, and non-permeated liquid is collected and transported to a pipeline (9), a part of the non-permeated liquid is extracted from the pipeline (9) and supplied to the distillation device (5), and the rest is sent to the heating device (3) through a circulation pipeline (10) for reheating and then circulated to the pervaporation device (4); the structure of the pervaporation membrane is a crown ether modified polyimide-nanofiber film-sodium alginate three-layer composite film.

9. The device according to claim 8, characterized in that: The nanofiber film is modified by low-temperature plasma.

10. The device according to claim 8, characterized in that: The filter membrane is an electronic grade filter membrane.

Citation Information

Patent Citations

  • Method for preparing electronic-grade isopropanol by virtue of ion exchange fibers and microporous membrane coupling columns

    CN103848718A